Epidemiology of cardiovascular disease - Reid, Christopher; Owen, A. (2016)
© Springer Science+Business Media Singapore 2016. All rights are reserved. Noncommunicable diseases such as cardiovascular diseases and cancers are key threats to maintaining health and well-being in the twenty-first century. In 2008, 30 % of global deaths were due to cardiovascular disease, a mortality burden felt by countries across the income/development spectrum. The middle of the twentieth century saw the advent of epidemiological studies which have made significant advances in understanding the factors driving cardiovascular disease risk. Studies such as the Seven Countries Study gathered data from across the globe on clinical and lifestyle factors and their relationship to rates of cardiovascular disease. Other landmark studies such as the Framingham Study set the scene for a detailed understanding of the magnitude of risk conferred by clinical factors. An increasingly sedentary lifestyle and energy-dense diet facilitated by urbanization have contributed to epidemics of obesity, hypertension, and diabetes, which are all major cardiovascular risk factors. These risks, coupled with aging populations (age being another key risk factor), drive the need to develop and implement prevention strategies that will be effective and accessible for high- and lower-income countries. The worldwide framework for tobacco control and workingwith the food industry to develop healthier accessible foods are key examples of lifestyle-related strategies for prevention. Low-cost preventivemedications such as the multicomponent "polypill" also hold promise as cost-effective strategies to reduce the burden of cardiovascular disease; however further evidence of the efficacy across different population and age groups is required.